PHENOMENA AND CHALLENGES OF LEARNING IN THE ERA OF DISRUPTION - Hermawan, Rakha; Ariga, Star; Rody Nst, Ahmad; Ulayya, Sajid; Sultan, M. Tife; Alimul Ammar, Muhammad (Proceeding International Seminar of Islamic Studies, 2023)
Islamic boarding schools are known as institutions that consistently teach and develop Islamic values. Challenges of Islamic Boarding School Education Institutions in the Era of Disruption. In the midst of such conditions, where people are increasingly being introduced to new changes, the existence of Islamic boarding schools is no doubt able to be adaptive in accepting the dynamics of life.Through a phenomenological approach and reflective logic, the pesantren's response to the dynamics of change is more comprehensively illustrated. One of the preparations that can be made is to improve the educational path and make it relevant in such a way that it is able to answer the needs of society and is able to imitate the signs of the times. Education in this country is also expected to be able to answer or fulfill people's needs and be able to catch the signs of the times.Islamic boarding schools have specifics that are much different from other institutions. Islamic boarding schools have a subculture that is related to a philosophy of life, a value system, and a system of power and authority in managing them. As the oldest education in Indonesia, Islamic boarding schools have at least 5 pillars, namely clerics, students, mosques, huts, and the yellow book. This article describes pesantren as educational institutions having a basic aspect called